Un exil, des combats : Les anarchistes espagnols parisiens dans la lutte antifranquiste (1945-1952) - Antoni Rossi Trafach (Cahiers de Civilisation Espagnole Contemporaine)
When France was liberated, the priority of the Spanish anarchists was to reconstitute the Spanish Libertarian Movement in Exile (MLE), before to continue the fight for freedom and bring down the dictatorship. Between 1945 and the beginning of the 1950’s, Spanish anarchists took an active part in the struggle against the Francoism and armed groups regularly crossed the Pyrenees. In order to finance actions in Spain, activists decided to reconstitute the Específica groups (FAI). In France, the growing number of expropriations ended up triggering a national investigation in which several police services collaborated. The investigation questioned the involvement of members of the MLE’s National Committee, which endangered the survival of the party on French territory. This article tries to show the central role played by the libertarian activists exiled in Paris in the revival of the anti-Franco struggle.